2018
DOI: 10.1080/14786419.2018.1478823
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activities of Ceiba speciosa (A.St.-Hil) Ravenna aqueous stem bark extract

Abstract: Several species of the genus Ceiba (Malvaceae) are ethnopharmacologically used. Thus, this study aimed to investigate the in vitro beneficial properties of the aqueous stem bark extract of Ceiba speciosa. The extract presented a great amount of phenolic compounds (117.4 ± 6.2 mg GAE/g). The antioxidant activity was assessed by DPPH (IC = 42.87 μg/mL), ORAC (2351.17 μmol TE/g) and FRAP (235.94 μM FeSO/g) methods. In addition, the extract reduced MCF-7 cell viability as assessed by MTT. However, it prevented mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Furthermore, the desire to increase fruit and vegetable consumption in the human diet is partially due to the favorable effects of beneficial antioxidants found in these foods on health promotion. Previous research on C. speciosa fruit and leaves has revealed anti-inflammatory and antioxidant properties [ 11 , 13 , 14 , 15 ], but whether FPCS, in addition to its role as a color additive, has similar activities was unknown before the current study.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, the desire to increase fruit and vegetable consumption in the human diet is partially due to the favorable effects of beneficial antioxidants found in these foods on health promotion. Previous research on C. speciosa fruit and leaves has revealed anti-inflammatory and antioxidant properties [ 11 , 13 , 14 , 15 ], but whether FPCS, in addition to its role as a color additive, has similar activities was unknown before the current study.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, a complex polymer with a backbone made up of glucuronosyl and mannosyl units has been found in the gum exudate, which is exuded when the trunk is injured [ 11 ]. C. speciosa fruit elicits anti-inflammatory and antioxidant responses via phenolic compounds that inhibit hydrogen peroxide-induced mitochondrial membrane depolarization and caspase-9 activation [ 11 , 13 ]. Preliminary research suggests that C. speciosa leaf extracts have antioxidant, anti-inflammatory, antipyretic, antibacterial and antifungal functions [ 14 , 15 ], while its seed oil shows hypoglycemic and anti-obesity properties [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first report on the antioxidant activity of fixed oil. Previously, Dörr et al [35] revealed that C. speciosa aqueous steam bark extract exerted a promising DPPH radical scavenging potential. A promising DPPH radical scavenging effect was observed, also by Krüger Cardoso Malheiros et al [36], who found percentage of 85.13 and 88.95% at concentration of 50 µg/mL for raw aqueous bark extract and ethanol extract, respectively.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…The C. grandifolia aqueous extract was screened for inhibition of p38 mitogen-activated protein kinase (MAPK) and Janus kinase 3 (JAK3). The inhibitory potency was assessed by previously established ELISA assays measuring the inhibition of p38α-mediated ATF-2 phosphorylation and JAK3-mediated ATP phosphorylation (Anastassiadis et al 2011;Dörr et al 2018;Goettert et al 2011Goettert et al , 2012. The half-maximal inhibitory concentration (IC 50 ) of the extract was calculated.…”
Section: Cell-free Kinase Assaymentioning
confidence: 99%